The trouble with counter-narratives - Ann-Sophie Hemmingsen; Karin Ingrid Castro (Danish Institute for International Studies (DIIS), 2017)
Counter-narratives are routinely suggested as responses to the vast amounts of propaganda available online, from groups such as Islamic State and al-Qaeda; and the idea of using them to prevent terrorism is gaining momentum. International organisations such as the EU and UN are including them in their CVE strategies, leading to a push for member states to do the same, in spite of a great deal of criticism and lack of any actual evidence that counter-narratives are an effective method. Taking its point of departure in three counter-narrative initiatives introduced in the third Danish national action plan on countering and preventing extremism and radicalisation, this report explores the challenges related to using counter-narratives within the Danish preventive framework in particular and in CVE strategies in general. The report finds that broad counter-narrative campaigns are neither necessary nor appropriate, and that the potential negative side-effects are not acceptable when measured against the expected benefits. The report ends by suggesting alternative approaches.
Keywords: 300